1998
DOI: 10.1111/j.1439-0523.1998.tb01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to Fusarium wilt (race 2) in chickpea

Abstract: The inheritance of resistance to Fusarium wilt (race 2) of chickpea was studied in a set of three crosses, i.e. 'WR315' x 'C104' (resistant x susceptible), 'WR315' x 'K85O' (resistant x tolerant) and 'K850' x 'GW5/7' (tolerant x tolerant) in order to investigate the number of genes involved, their complementation and to find out whether resistant segregants are possible in a cross between two tolerant cultivars. Tests of Fl, F2 and F3 generations of these crosses under controlled conditions at ICRISAT, Patanch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Likewise, other researchers have reported digenic inheritance for other races (0 and 2) of Foc (Tullu et al, 1999;Rubio et al, 2003). Previously, the digenic (a, b) nature of Foc2 resistance was also established based on the disease reaction of F 2 and F 3 individuals derived from WR 315 × C 104 (Kumar, 1998). Whereas Tekeoglu et al (2000) and Sharma et al (2004) reported monogenic inheritance of Foc 3 and Foc 5 resistance.…”
Section: Inheritance Of Fw Resistance In Grain Legumesmentioning
confidence: 89%
See 3 more Smart Citations
“…Likewise, other researchers have reported digenic inheritance for other races (0 and 2) of Foc (Tullu et al, 1999;Rubio et al, 2003). Previously, the digenic (a, b) nature of Foc2 resistance was also established based on the disease reaction of F 2 and F 3 individuals derived from WR 315 × C 104 (Kumar, 1998). Whereas Tekeoglu et al (2000) and Sharma et al (2004) reported monogenic inheritance of Foc 3 and Foc 5 resistance.…”
Section: Inheritance Of Fw Resistance In Grain Legumesmentioning
confidence: 89%
“…Notably, resistance to wilt is an essential prerequisite for variety identification and release in pigeonpea. Several pigeonpea varieties such as Asha (ICPL , 1998;Castillo et al, 2003 Chickpea Andoum 1 and Ayala (race 0) - Halila and Harrabi, 1990;Landa et al, 2006 Chickpea Surutato-77, Sonora-80, Tubutama, UC-15 and UC-27, Gavilan Mexico Morales, 1986;Buddenhagen et al, 1988;Helms et al, 1992;Sharma et al, 2005 Chickpea (Singh I. P. et al, 2016;Bohra et al, 2017).…”
Section: Plant Genetic Resources For Fw Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Late wilting resistance is conferred by any one of these three genes, but a combination of any two of the late wilting genes confers complete resistance (h1h2 or h1H3 or h2H3) [12,23]. A similar genetic system based on two [70] or three [71] independent genes was found to confer resistance to race 2 [70,71]. Sharma et al [51] demonstrate that resistance to race 2 is governed by a single recessive gene, whereas resistance to race 3 has been found to be monogenic [51,72].…”
Section: Resistance To Fusarium Wiltmentioning
confidence: 99%